2009
DOI: 10.1063/1.3237028
|View full text |Cite|
|
Sign up to set email alerts
|

Accurate ab initio potential energy curves for the classic Li–F ionic-covalent interaction by extrapolation to the complete basis set limit and modeling of the radial nonadiabatic coupling

Abstract: Multireference configuration interaction calculations using large correlation consistent basis sets and full configuration interaction calculations with the smallest of such basis are utilized to describe the ionic-neutral curve crossing for the title system. The results of the former calculations have then been extrapolated to the complete basis set limit using the uniform singlet- and triplet-pair extrapolation scheme. A recent suggestion for locating the nonadiabatic matrix terms at the point where the dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 56 publications
1
41
0
Order By: Relevance
“…A slight hump appears in V 12 at the location of maximum adiabatic interaction but much less peaked than before. 1 An enhanced similarity with other curves 2-5 is apparent. Upon diagonalization, the adiabats are exactly reproduced.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…A slight hump appears in V 12 at the location of maximum adiabatic interaction but much less peaked than before. 1 An enhanced similarity with other curves 2-5 is apparent. Upon diagonalization, the adiabats are exactly reproduced.…”
mentioning
confidence: 64%
“…(26) of Ref. 1. Although fits to the calculated NACTs using both a Lorentzian form (L1) and sums of up to three logistic functions (for the cumulative probability) or bell-shaped curves (for the transition probability) have been reported, 1 only the latter (denoted S3, with components S3-A, S3-B, and S3-C) will be considered here.…”
mentioning
confidence: 99%
“…The work by Varandas [24] on LiF has shown that this quality of basis set can achieve an accuracy within 1% of the complete basis set (CBS) limit. The simplest calculations performed used DFT and a variety of exchange functionals in an attempt to model the entrance and exit channels of the ground potential energy surface and to determine the minimum energy geometry of the M 2 + X reactions Li 2 + [F, Cl, Br] and F + [Na 2 , K 2 ].…”
Section: Ab Initio Methodsmentioning
confidence: 99%
“…Theoretical studies on LiF in recent years include static ab initio calculation of PESs [45,46], and calculations of field-induced dynamics [47,48]. To the best of our knowledge, no experimental study on its field-induced dynamics has ever been reported, but it still serves as a prototype for studying an interplay of field-induced and intrinsic nonadiabatic transitions.…”
Section: A Systems and Computational Detailsmentioning
confidence: 99%